1714. Influenza C Virus in U.S. Children with Acute Respiratory Infection 2016-2019. (31st December 2020) - Sederdahl, Bethany K; Weinberg, Geoffrey A; Campbell, Angela P; Selvarangan, Rangaraj; Schuster, Jennifer E; Harrison, Christopher J; Rha, Brian; Lively, Joana Y; Patel, Manish; Shu, Bo; Boom, Julie A; Avadhanula, Vasanthi; et al.
Abstract: Background: Influenza C virus (ICV) is associated with acute respiratory infection (ARI); however, the burden of ICV is not well-described. We sought to determine the burden and characteristics of ICV in a prospective, population-based cohort. Methods: The study was conducted within the New Vaccine Surveillance Network (NVSN), a CDC-led, seven-site network that performs population-based surveillance for ARI in children < 5 years. Nasal/throat swabs were collected from emergency department (ED) or inpatient children with ARI, or healthy controls in clinic, between 12/05/2016-10/31/2019 and tested by real-time RT-PCR for ICV and other respiratory viruses. Preliminary data were extracted and demographic/clinical features of ICV+ cases analyzed. We sequenced the hemagglutinin-esterase (HE) gene from ICV+ Pittsburgh samples. Results: Among 19, 321 children with ARI or healthy controls enrolled and tested for ICV from 2016-2019, 115/17, 668 (0.7%) ARI cases and 8/1653 (0.5%) healthy controls tested positive for ICV. The median age of ICV+ ARI subjects was 19 months (IQR 10, 46) and 81(70%) were ≤36 months. 42.6% (49) were white, 33.9% (39) black, and 16.5% (19) Hispanic, with the remainder Asian or unknown; 56.5% (62) attended daycare. Among ICV+ ARI cases, 67.8% (78) had fever, 94.8% (109) cough, and 60.8% (70) wheezing. 45.2% (52) ICV+ cases occurred in 2016-17, 6.5% (8) in 2017-2018, and 47.8% (55) in 2018-19 (Table ). 40% (46) of ICV+ cases were seen in the ED, while the remainder were inpatients. Median length of stay was 2d (IQR, 1-3) with 15 admitted to ICU. 67.8% (78/115) ARI cases had 1 or 2 co-detected pathogens, with rhinovirus (26), respiratory syncytial virus (26), and adenovirus (14) most frequently co-detected. ARI symptoms including fever, myalgias, chills, and wheezing did not differ significantly between coinfected subjects and those who were only ICV+. HE sequences were in the two currently circulating Kanagawa and Sao Paulo lineages. ICV+ Cases by Site and Year Conclusion: ICV was an uncommon cause of ARI symptoms leading to healthcare encounters in young children. The prevalence varied year-to-year and between different geographic regions. Most children infected with ICV were ≤3 years old and had co-detected pathogens. ICV was similarly rarely detected in healthy controls. Disclosures: Christopher J. Harrison, MD, GSK (Grant/Research Support, Infant menigiciccal B conjugate vaccine trial)Merck (Research Grant or Support, Infant pneumococcal conjugate vaccine trial) Natasha B. Halasa, MD, MPH, Genentech (Other Financial or Material Support, I receive an honorarium for lectures - it's a education grant, supported by genetech)Karius (Consultant)Moderna (Consultant)Quidel (Grant/Research Support, Research Grant or Support)Sanofi (Grant/Research Support, Research Grant or Support) John V. Williams, MD, GlaxoSmithKline (Advisor or Review Panel member)IDConnect (Advisor or Review Panel member)Quidel (Advisor or Review Panel member)